Umieranie i rodzenie się do nowego życia. Obrzędy – zwyczaje – symbole - Rotter, Lucyna (Warstwy, 2017)
The process of our dying starts the moment we are born. This is an obvious truth, though usually put aside from our conscious thoughts. Throughout human life death and birth merge, if not complement each other. The task of rituals and ceremonies is often to make one used to the fear of death and to emphasize the joy of birth. At the same time the death-birth dichotomy appears in a lot of situations. When a stage of life ends, something new begins. This is the case both in the domain of the sacred and the profane. Rituals, ceremonies and symbols related to the wedding include signs referring to chastity and joy as well as to death and evil. It is similar with the symbols referring to death and mourning. As regards the sphere of the sacred, this process is best seen in the rituals connected with monastic life. Dying to the world and being born to a new life devoted to God is clearly present in the symbols connected with being ordained and taking the religious vows.